Lack of effect of antineutrophil cytoplasmic antibodies associated with ulcerative colitis on superoxide anion production from neutrophils. Issue 1 (January 1997) - Gionchetti, P; Vecchi, M; Rizzello, F; Ferretti, M; Calabresi, C; Venturi, A; Bianchi, M B; Brignola, C; Sinico, R A; De Franchis, R; Miglioli, M; Campieri, M
Abstract : BACKGROUND: Antineutrophil cytoplasmic antibodies (ANCAs) from patients with vasculitidis can induce neutrophils to release oxygen radicals in vitro. ANCAs with a perinuclear pattern of immunofluorescence are found in most patients with ulcerative colitis, but several findings are against ANCAs having a pathogenetic role in this disease. AIMS: To evaluate the influence of ANCAs associated with ulcerative colitis on the respiratory burst activity of neutrophils. PATIENTS: Serum samples were obtained from 14 patients with ulcerative colitis, seven of whom showed positivity for p-ANCAs, three patients with vasculitidis, two with positivity for p-ANCAs, and one for c-ANCAs, and seven healthy volunteers. METHODS: A positive ANCA serology was determined with a standard indirect immunofluorescence assay. Purified immunoglobulins (IgGs) were prepared from serum samples by DEAE-Affigel blue chromatography. Human neutrophils were prepared by dextran-Ficoll-Hypaque separation. Superoxide anion (O2-.) generation was measured by following the superoxide dismutase inhibitable reduction of ferricytochrome. RESULTS: There were no significant differences among samples from ulcerative colitis IgG p-ANCA positive, ulcerative colitis IgG p-ANCA negative patients, and controls on O2-. production, whereas ANCA positive IgG from vasculitidis significantly enhanced O2-. release (p < 0.001). CONCLUSIONS: p-ANCAs associated with ulcerative colitis have no effect on the respiratory burst activity of normal human neutrophils in vitro. These results reinforce the hypotheses that ANCAs are unlikely to contribute to the pathogenesis of ulcerative colitis.